INTERAKSI KOMUNIKASI KELOMPOK PADA KOMUNITAS BOGOR RUNNERS - Habsyah, Habsyah; ratnamulyani, ike atikah; kusumadinata, ali alamsyah (JURNAL KOMUNIKATIO, 2020)
This study aimed to determine the interaction in group communication in the Bogor Runners community. The study used a method with a descriptive quantitative approach and was tested by Rank Spearman correlation. The research sample was 56 members of the Bogor Runners Community who were taken using accidental sampling technique. The results of the study indicate that (1) Shaking hands when meeting other members, (2) Giving a smile when meeting other members, (3) Making a telephone conversation when not meeting directly with other members, (4) Pleasing and open when communicate with other members, (5) Share running sports experiences with other members, (6) Give opinions in discussion activities. Interactions that occur in the group communication process have an interpretation rate of 4.33 and are in a very good category.Keywords: Interaction, Community, Group Communication.